Teachers’ understanding of mathematical cognition in childhood: Towards a shift in pedagogical content knowledge? - Elizabeth Henning (Perspectives in Education, 2013)
This article about the discourse of pedagogy as related to child cognition in mathematics addresses the issue of what constitutes the main disciplinary content and the pedagogical content knowledge (PCK) of foundation-phase teachers. I argue that, unless child cognition itself is the primary disciplinary content of foundationphase teachers’ knowledge, it is likely that they will couch their pedagogical knowledge in teaching methods and materials more than in knowledge of conceptual development of learners and how such knowledge relates to teaching. In this first of a series of case studies, workshop-generated conversational and interview data were analysed qualitatively for discourse. The topics for the workshops were mathematical cognition and training in standardised test administration. The analysis showed that the discourse of teachers’ expressed knowledge about their practice was embedded in the language of policy, curriculum, teaching methods of mathematics, and the omniscience of the annual national assessments (ANAs) in South Africa, with very few discourse markers representing knowledge of child cognition. During the course of the intervention, teachers gradually shifted their talk, expressing some understanding of trends in contemporary developmental cognitive psychology and neuroscience of mathematical cognition. The article recommends a stronger cognitive science focus in teacher professional development initiatives.